Assessing the level of knowledge, practical skills and self-confidence of anesthesia residents in the field of Cardiopulmonary Cerebral Resuscitation by academic year of Shiraz University of Medical Sciences in 2018 - Mansoor Masjedi; Razieh Neshatavar; Leila Moeini; Elahe Allahyary; Narges Sadat Dorijani (Mashhad University of Medical Sciences, 2021)
Background: Training plays a pivotal role in correct implementation of Cardiopulmonary Resuscitation (CPR). Ideal training affects, Knowledge, attitude and skills of the trainees. CPR is amongst the most important and essential topics in residency training program, especially in the field of anesthesia. The aim of this study was to evaluate knowledge, attitude and skill of anesthesia residents according to their own opinion.Methods: This study was a cross-sectional census and included anesthesiology residents of first to fourth post graduate year (PGY). Assistants who were reluctant to participate or answer all the questions were not included. Also, informed consent was obtained. The data collection instrument was a 45-item, five-choice researcher-made Likert scale questionnaire. The questionnaires were distributed among anesthesia residents and gathered after completion for analysis.Results: There were 63 participants in the study. Age and knowledge level of the four groups did not show significant differences. The level of knowledge and skills of the first and second year, first and third year and first and fourth year residents were significantly different. The level of skills and self-confidence of first and second year residents was significantly different from the third and fourth year. The attitude toward level of importance of training in operating room was not significantly different among the four PGYs. Above 85% of the first to fourth year residents agreed with the importance of learning resuscitation in the ICU, and its six and twelve months' repetition. Conclusion: The level of knowledge, practical skills and self-confidence of anesthesia residents in the field of cardiopulmonary resuscitation increases in accordance with advancement of post graduate year.